The role of high-dose, single-fraction irradiation in small and large intracranial arteriovenous malformations - Engenhart, Rita; Wowra, Berndt; Debus, Jürgen; Kimmig, Bernhard; Höver, Karl-Heinz; Lorenz, Walter Josef; Wannenmacher, Michael (International journal of radiation oncology, biology, physics, 1994)
Purpose: Radiosurgery with external beam irradiation is an accepted treatment for small intracranial vascular malformations. It has been proven effective and safe for lesions with volumes of less than 4 cc. However, there is only some limited clinical data for malformations of grade 4 and grade 5, according to Spetzler and Martin. Methods and Materials: At the Heidelberg radiosurgery facility equipped with a linear accelerator, 212 patients with cerebral arteriovenous malformations have been treated since 1984. Thirty-eight percent of the arteriovenous malformations treated were classified inoperable, 14% grade 5, 19% grade 4, and 29% grades 1-3. Radiation doses between 10 and 29 Gy were applied to the 80% isodose contour. Results: Above a threshold dose of 18 Gy, the overall obliteration rate was 72%. After 3 years, the obliteration rates were 83% with volumes of less than 4.2 cc, 75% with volumes of up to 33.5 cc, and 50% with volumes of up to 113 cc. Of the patients presenting with seizures and paresis, 83% and 56%, respectively, showed improvement, which correlated with the degree of obliteration. After a follow-up period of up to 9 years, the rate of radiation-induced severe late complications was 4.3%. In grade 5 lesions, the risk of side effects was 10%. No serious complications occurred if a maximum dose of less than 25 Gy was applied to treatment volumes of less than 33.5 cc. Conclusion: The success of stereotactic high-dose irradiation of arteriovenous malformations depends on the dose applied. The incidence of radiation-induced side effects increased with the applied dose and treatment volumes. From our experience, doses of less than 25 Gy and treatment volumes of up to 33.5 cc are safe and effective. In the future, new techniques of radiosurgery with linear accelerators and dynamically reshaped beams will allow us to apply homogenous dose distributions. Additional use of magnetic resonance angiography for 3D treatment planning will help to identify the nidus more easily.
Gesehen am 17.12.2024
Elektronische Reproduktion der Druck-Ausgabe 22. Dezember 2009